Economics - N. Gregory Mankiw; Mark P. Taylor (Singapore Cengage Learning EMEA, 2019)
Now firmly established as one of the leading economics principles texts in the UK and Europe, this exciting, new fifth edition of Economics by N. Gregory Mankiw (Harvard University) and Mark P. Taylor (Washington University), has been fully updated. Much revered for its friendly and accessible approach, emphasis on active learning, and unrivalled support resources, this edition also has an improved structure to ensure the text aligns even more closely with the latest courses. The new edition incorporates additional coverage of a number of key topics including heterodox theories in economics such as complexity theory; institutional economics and feminist economics; different theories in international trade; game theory; different measures of poverty; the 'flat Phillips curve'; and the future of the European Union. This title is available with MindTap, a flexible online learning solution that provides students with all the tools they need to succeed including an interactive eReader, engaging multimedia, practice questions, assessment materials, revision aids, and analytics to help you track their progress.
Keywords: Economics; Textbooks; (UGB-109) Economics